Marketing Strategy Analysis Based On SWOT At PT. Muba Link Business Unit Of Wisma Ranggonang - Anggraini, Desi Ulpa; Hafid, Harapin; Zainuddin, Periansya; Alamsyah, Rully (STAI Miftahul Ula Nganjuk, 2017)
The purpose of this research was to know and analyze the marketing strategy based on SWOT analysis at PT. Muba Link Business unit Wisma Ranggonang Sekayu district Musi Banyuasin.  The population of this research were the leadership and the employees of Wisma Ranggonang.  This research was conducted by using descriptive research method with a quantitive approach in the form of quadrant position analysis by using SWOT Matrix analysis and after that it was proceed with the decision of making phase in the form of marketing strategy. The result showed that based on the external/internal Matrix get value of each strength factor for about 1, weakness is 1.25 opportunity worth 1,285 and threat is 1,217. Meanwhile, based on cartesius diagram, the quadrant position of Wisma Ranggonang Sekayu was in the third quadrant supporting the turnaraound strategy, i.e. the company faces a huge market opportunity, but on the other hand it faces some internal conctraints/weakness. The focus of this companyâs strategy was to minimize the internal company problems, so as to seize the more market opportunities. So, the initial hypothesis that Wisma Ranggonang Sekayu supports the growth/aggressive strategy was not fulfilled.